Effects of aerobic exercise on memory and executive related brain regions volume and function in healthy older adults: a systematic review with meta-analysis - VERA, ROBERTO (Usach, 2025)
Introduction: Aerobic exercise (AE) may counteract aging effects by improving hippocampal and prefrontal cortex (PFC) volumes and cognitive function; however, clinical studies often overlook the connection between structural and functional changes. Objective: To assess the effects of AE on hippocampal and PFC volumes and their impact on cognitive functions in healthy older adults. Methods: A systematic search was conducted in MEDLINE, Embase, and CENTRAL until June 2024. Randomized controlled trials (RCTs) including cognitively healthy adults undergoing AE interventions were included. Outcomes were changes in hippocampal or PFC volumes (fMRI) and cognitive functions. Risk of bias was assessed using the RoB 2 tool, and certainty of evidence evaluated with GRADE. Results: Out of 5857 records screened, four studies involving 320 participants were included. AE interventions lasted 3–12 months, with 2–3 weekly sessions of 15–60 minutes at moderate intensity. Meta-analysis of hippocampal volume showed an SMD of 0.24 (95% CI, -0.08 to 0.55, very low certainty). One study evaluated PFC volume, showing no significant changes. Cognitive functions assessed included executive function and memory, with general improvements but high heterogeneity. All studies had a high risk of bias. Conclusions: AE may have uncertain effects on hippocampal volume and minimal impact on PFC but appears to improve cognitive functions, likely driven by functional and neurochemical changes rather than volumetric alterations. Mechanisms such as neurogenesis, synaptic plasticity, and vascular health may be involved. Future studies should standardize assessments, expand sample sizes, and investigate neurochemical pathways.
Keywords: Ciencias Biológicas